Management of Spacing in Mandibular Anterior Teeth by Minimally Invasive Technique Using Laminates: A Case Report - Agrawal, Hema; Singh, RK; Suwal, P; Parajuli, P; Limbu, IK; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2019)
People have become increasingly concerned about esthetics as a perfect smile gives patients more confidence and make them feel comfortable in social circumstances. Esthetic dental treatment plays an important role in improving personal appearance. Advances in dental materials have led to innovations in porcelain laminate veneers and bonding materials which has improved the overall quality of the esthetic restorations. This case report describes the rehabilitation of a patient with spacing in mandibularanterior teeth, who was concerned with his facial appearance, with ceramic laminate veneers.